The Relationship between God and Man in Proverbs - Kidner, F. D. (1960)
An exploration of how the relationship between God and humans is developed in Proverbs, paying attention to the interplay of moral and religious dimensions with wisdom.
Keywords: Proverbs; Wisdom; Old Testament